2008
DOI: 10.1111/j.1574-6968.2008.01163.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of qnr-positive clinical isolates in Klebsiella pneumoniae producing ESBL or AmpC-type β-lactamase from five pediatric hospitals in China

Abstract: The plasmid-mediated quinolone resistance qnr genes in clinical isolates in adults have been described in different countries; however, the frequency of their occurrence has not been detected in pediatric patients. A total of 410 clinical isolates of Klebsiella pneumoniae, identified as producers of an extended-spectrum beta-lactamase (ESBL), or AmpC beta-lactamase, were collected from five children's hospitals in China during 2005-2006. The isolates were screened for the presence of the qnrA, qnrB, and qnrS g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 30 publications
3
19
2
1
Order By: Relevance
“…Studies have shown that Extended-Spectrum Beta-Lactamase (ESBL)-producing Klebsiella pneumoniae have rapidly spread worldwide and pose a serious threat for health care-associated infections [1] . Increasingly the ESBL Klebsiella pneumoniae are also showing co-resistance to quinolones and aminoglycoside antibiotics [5,6] present in plasmids which can be transferred by conjugation to other strains.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that Extended-Spectrum Beta-Lactamase (ESBL)-producing Klebsiella pneumoniae have rapidly spread worldwide and pose a serious threat for health care-associated infections [1] . Increasingly the ESBL Klebsiella pneumoniae are also showing co-resistance to quinolones and aminoglycoside antibiotics [5,6] present in plasmids which can be transferred by conjugation to other strains.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the quinolone resistance-determining region (QRDR) and the presence of plasmidmediated quinolone resistance (PMQR) genes contribute to quinolone resistance in complex and diverse ways (1)(2)(3). However, only limited studies have addressed the quinolone resistance of Enterobacteriaceae in pediatric isolates so far; long-term studies involving bloodstream isolates are even fewer in number (4)(5)(6).…”
mentioning
confidence: 99%
“…A plasmid carrying a PMQR gene is transferable to other organisms, which facilitates the selection of high-level resistance (13). Previous studies showed an association between PMQR gene-bearing plasmids and plasmids with ESBL, suggesting the association with resistance to other agents (4). PMQR genes were first described in a clinical isolate of K. pneumoniae in 1998 (14).…”
mentioning
confidence: 99%
“…Lin J-C, Chang F-Y, Fung C-P, Xu J-Z, Cheng H-P, Wang J-J, et al fluoroquinolones (15,16). The excessive use of antibiotics has further increased the incidence of antibiotic resistance in bacteria, resulting in treatment failure, development of complications, and increased cost of treatment (17).…”
Section: Conflict Of Interestmentioning
confidence: 99%